If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 + -5X = 13X + 22 Reorder the terms: 52 + -5X = 22 + 13X Solving 52 + -5X = 22 + 13X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-13X' to each side of the equation. 52 + -5X + -13X = 22 + 13X + -13X Combine like terms: -5X + -13X = -18X 52 + -18X = 22 + 13X + -13X Combine like terms: 13X + -13X = 0 52 + -18X = 22 + 0 52 + -18X = 22 Add '-52' to each side of the equation. 52 + -52 + -18X = 22 + -52 Combine like terms: 52 + -52 = 0 0 + -18X = 22 + -52 -18X = 22 + -52 Combine like terms: 22 + -52 = -30 -18X = -30 Divide each side by '-18'. X = 1.666666667 Simplifying X = 1.666666667
| (x+2)/2+(x-3)/3=20 | | 2/y-6 | | -8+1/2y=2 | | 2x-7x+5-3=x+8x-3 | | x+2.4=2x+1.7 | | y=21/2 | | 133-5X=10X+23 | | 4x(2x-4y)=9 | | -4(3-x)= | | 1/2+5/10 | | 4x(2x-5x)=4 | | 2X+14=56-4 | | (3/4)*x-1=(1/2)*x+2 | | N*7+13=90 | | 23=10-6x | | 2x-(3-x)=4 | | 61-6x=3x+18 | | 5x7/8 | | 10x-7=16x+5 | | 1+7/16/3+9/16 | | 314=3.14*r^2 | | n+5*3=36 | | n+5*3=26 | | 5n+3n=-40 | | 7n-13=36 | | 3x+6+2x-8=x-3x-9 | | (n-8)*8=40 | | 2+2i=0 | | 6x+7=-97-8x | | 4x-13/11=5 | | 7(2p+3)-7=6p+29 | | 2x-3y=-12fory |